2017
DOI: 10.1371/journal.pone.0185989
|View full text |Cite
|
Sign up to set email alerts
|

Striatal astrocytes engulf dopaminergic debris in Parkinson's disease: A study in an animal model

Abstract: The role of astrocytes in Parkinson’s disease is still not well understood. This work studied the astrocytic response to the dopaminergic denervation. Rats were injected in the lateral ventricles with 6-hydroxydopamine (25μg), inducing a dopaminergic denervation of the striatum not accompanied by non-selective tissue damage. The dopaminergic debris were found within spheroids (free-spheroids) which retained some proteins of dopaminergic neurons (e.g., tyrosine hydroxylase, the dopamine transporter protein, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 49 publications
(58 reference statements)
5
40
0
2
Order By: Relevance
“…In agreement with a previous study (Morales et al, 2017), no accumulation of the cytosolic SNARE protein syntaxin 17 (STX17) was observed in spheroids (see C 1 /C 3 and C 4 /C 6 in Figure 4), which, on the other hand, showed LC3‐puncta (D 1 /D 5 ) but not STX17 immunoreactivity (D 1 /D 5 ). The present study showed that spheroids also present no immunoreactivity for the polyubiquitin chains linked by the Lysine 48 (UbiK48) (E 4 /E 6 in Figure 5), an absence that cannot be attributed to methodological problems because the same slices showed the UbiK48 immunoreactivity expected for this protein in the soma of astrocytes (yellow arrows in E 1 –E 3 ) and of other striatal cells (green arrow in E 1 –E 3 ).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with a previous study (Morales et al, 2017), no accumulation of the cytosolic SNARE protein syntaxin 17 (STX17) was observed in spheroids (see C 1 /C 3 and C 4 /C 6 in Figure 4), which, on the other hand, showed LC3‐puncta (D 1 /D 5 ) but not STX17 immunoreactivity (D 1 /D 5 ). The present study showed that spheroids also present no immunoreactivity for the polyubiquitin chains linked by the Lysine 48 (UbiK48) (E 4 /E 6 in Figure 5), an absence that cannot be attributed to methodological problems because the same slices showed the UbiK48 immunoreactivity expected for this protein in the soma of astrocytes (yellow arrows in E 1 –E 3 ) and of other striatal cells (green arrow in E 1 –E 3 ).…”
Section: Resultssupporting
confidence: 93%
“…Similarly to that previously reported (Morales et al, 2017), the puncta shape (A 7 and A 8 in Figure 4) of the microtubule‐associated protein 1 light chain 3 (LC3) immunoreactivity (A 2 and A 6 ) found in the spheroids (A 1 /A 5 ) of rats suggests that these structures may generate autophagosomes (see also Supporting Information Movie S3). In the present study, the YFP‐Mito‐DAn mouse provided similar findings (bottom Figure 4), showing puncta shape LC3 immunoreactivity (E 3 , E 6 , and E 7 ) in DAergic spheroids (E 1 and E 4 ) containing YFP (E 2 and E 5 ).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations